The battle for the Arab Spring : revolution, counter-revolution and the making of a new era - Noueihed, Lin; Warren, Alex (Yale University Press, 2013)
"The Arab Spring of 2011 unleashed a torrent of hope, change -- and conflict. A year on, the excitement of new freedoms has given way to a complex picture ranging from gradual democratization to vicious repression, and a mounting frustration that, despite transformations in the pollitical sphere, the daily lives of most people in the region have yet to see an improvement. With the aid of first-hand reporting, Lin Noueihed and Alex Warren analyse the extraordinary repercussions of early 2011 and uncover the competing forces vying for dominance in the region. Assecular parties have failed to take advantage of the new opportunities, Islamists (some apparently moderate, some less so) have surged to the fore, offering a focus on honesty, justice and conservative values which appeals to ordinary people tired of years of corruption and repression. Meanwhile, the authoritarian regimes who controlled the region for decades have in most cases yet to release their grip -- whether in the form of Syria's attempts to quash rebellion or the subtler machinations ofthe Egyptian military. Less reported has been the Saudi role in suppressing popular protest in Bahrain, tacitly supported by Western powers who at the same time poured resources into ending Gaddafi's reign in Libya. As tensions mount and the global economic situation worsens, Noueihed and Warren ask: where next for the Arab world?"-- Book jacket